THEORETICAL FOUNDATIONS OF COSTS - Dzhumaeva Guzal Akhtamovna, (TADQIQOTLAR, 2025)
Abstract:  The  article  discusses  international  standards  of  provision,  the corresponding classification of education in national practice and ensuring security in international practice.